2018
DOI: 10.1080/17518369.2018.1540243
|View full text |Cite
|
Sign up to set email alerts
|

Warm-water events in the eastern Fram Strait during the last 2000 years as revealed by different microfossil groups

Abstract: The environmental system of the northern Nordic Seas is very sensitive to oceanographic and climatic changes at the contact of cold Arctic and warmer North Atlantic waters. These contrasts are reflected in the associations of marine microorganisms and archived in the bottom sediments. A microfossil study (diatoms, coccoliths) of late Holocene sediments in core MSM5/5-712-1 from the eastern Fram Strait provides a better understanding of marine ecosystems and palaeoenvironments during Arctic warming events of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Climatic periods and their timing defined historically in north-western Europe by Lamb (1977) correlate with major changes in proxy records in the North Atlantic and Nordic seas region. They indicate temperature and productivity changes on multidecadal to centennial timescales with prominent cold and warm anomalies (e.g., Jiang et al 2002;Spielhagen et al 2011;Andresen et al 2013;Matul et al 2018). Increased inflow of warm subsurface Atlantic Water from the Norwegian Sea into the Arctic Ocean via the eastern Fram Strait is considered to be responsible for the warm intervals associated with the Roman Warm Period, the Medieval Climate Anomaly and the Recent Warming (Spielhagen et al 2011;Werner et al 2011;Zamelczyk et al 2013;Werner et al 2016).…”
Section: Late Holocene Changes In Water-mass Properties and Productivmentioning
confidence: 99%
See 2 more Smart Citations
“…Climatic periods and their timing defined historically in north-western Europe by Lamb (1977) correlate with major changes in proxy records in the North Atlantic and Nordic seas region. They indicate temperature and productivity changes on multidecadal to centennial timescales with prominent cold and warm anomalies (e.g., Jiang et al 2002;Spielhagen et al 2011;Andresen et al 2013;Matul et al 2018). Increased inflow of warm subsurface Atlantic Water from the Norwegian Sea into the Arctic Ocean via the eastern Fram Strait is considered to be responsible for the warm intervals associated with the Roman Warm Period, the Medieval Climate Anomaly and the Recent Warming (Spielhagen et al 2011;Werner et al 2011;Zamelczyk et al 2013;Werner et al 2016).…”
Section: Late Holocene Changes In Water-mass Properties and Productivmentioning
confidence: 99%
“…Increased inflow of warm subsurface Atlantic Water from the Norwegian Sea into the Arctic Ocean via the eastern Fram Strait is considered to be responsible for the warm intervals associated with the Roman Warm Period, the Medieval Climate Anomaly and the Recent Warming (Spielhagen et al 2011;Werner et al 2011;Zamelczyk et al 2013;Werner et al 2016). However, depending on the environmental settings, proximity of the sea-ice edge, availability of nutrients, microfossil types and other proxies, the productivity signals may vary considerably (Matul et al 2018;Moffa-Sánchez et al 2019). We compare our temperature estimates and flux of the subsurface dwelling N. pachyderma and near-surface to surface living T. quinqueloba and G. uvula as indicators of subsurface and near-surface to surface water productivity, respectively, to other records based on planktic foraminifera and other microfossils indicative of biological production in Fram Strait and northern North Atlantic (Figs.…”
Section: Late Holocene Changes In Water-mass Properties and Productivmentioning
confidence: 99%
See 1 more Smart Citation
“…This species was observed by a Continuous Plankton Recorder (CPR) survey in the Atlantic Ocean in 1999, seemingly its first occurrence in the Atlantic for millennia, and Reid et al () proposed accelerated connectivity due to reduced sea ice cover as an explanation. Subsequent analysis of sediment cores has suggested that, although not found in any CPR surveys prior to 1999, the species may in fact have been present in the Fram Strait as early as 1989 (Matul et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Small glaciers also have impacts on river discharge and energy exchange within basins (Verbunt et al 2003). Svalbard (10°-35°E, 74°-81°N) is located in close proximity to the warm West Spitsbergen Current (Matul et al 2018), and the mass balance of glaciers in the archipelago is very sensitive to fluctuations in this current and the corresponding climate changes (Xu et al 2007). At present, Svalbard is an international hotspot for glacier research.…”
Section: Introductionmentioning
confidence: 99%